The status, challenges, and trends: an interpretation of technology roadmap of intelligent and connected vehicles in China (2020) - Xu, Qing; Li, Keqiang; Wang, Jianqiang; Yuan, Quan; Yang, Yanding; Chu, Wenbo (Journal of Intelligent and Connected Vehicles, 2022)
Purpose The rapid development of Intelligent and Connected Vehicles (ICVs) has boomed a new round of global technological and industrial revolution in recent decades. The Technology Roadmap of Intelligent and Connected Vehicles (2020) comprehensively analyzes the technical architecture, research status and future trends of ICVs. The methodology that supports the roadmap should get studied. Design/methodology/approach This paper interprets the roadmap from the aspects of strategic significance, technical content and characteristics of the roadmap, and evaluates the impact of the roadmap on researchers, industries and international strategies. Findings The technical architecture of ICVs as the “three rows and two columns” structure is studied, the methodology that supported the roadmap is explained with a case study and the influence of key technologies with proposed development routes is analyzed. Originality/value This paper could help researchers understand both thoughts and methodologies behind the technology roadmap of ICVs.